PENGARUH KEPUASAN PELANGGAN, KEPERCAYAAN PELANGGAN DAN SWITCHING BARRIERS TERHADAP LOYALITAS PELANGGAN (Studi Kasus Pada Toko Ogan Malang) - Danang Adi Saputro; Muhammad Hufron; Afi Rachmat Slamet (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACTTarget this research is to know influence customer satisfaction, customer trust and Switching Barriers by simultan to loyality Ogan Shop Malang. To know influence customer satisfaction, customer trust and Switching Barriers by partial to loyality Ogan Shop Malang.This type Research is explanatory research. This research done at Ogan Shop Malang. Population in this research is customer of Ogan Shop Malang Start december month 2016 up to May 2017 with grand total is 4.320. While sampel in this research counted 98 responder. Result of research indicate that variable customer satisfaction, customer trust and Switching Barriers have an effect by simultan to loyality Ogan shop Malang. Variable customer satisfaction, customer trust and Switching Barriers have an effect by partial to loyality Ogan shop Malang. Keyword: customer satisfaction, customer trust and Switching Barriers and customer loyality